1982
DOI: 10.1177/0022002182013002001
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of Intelligent Behavior

Abstract: The cross-cultural generalizability of two Western intelligence tests, the Stanford-Binet and the WAIS, in a non-Western culture was examined. Samples of 976 Australian and 1003 Chinese university and high school students participated in a rating task. Items from the two tests were given to students, and were rated on the two aspects of relevance and difficulty. On relevance ratings, the underlying three-factor structure of the Chinese sample accords very well with that of the Australian, suggesting a basic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The Chinese-language-schooled group, however, tended to rate verbal skills as less important than did the English-language-schooled group. Moreover, in an earlier study, Chen, Braithwaite, and Huang (1982) found that Chinese students viewed memory for facts as important for intelligence, whereas Australian students viewed these skills as of only trivial importance. Das (1994), also reviewing Eastern notions of intelligence, has suggested that in Buddhist and Hindu philosophies, intelligence involves waking up, noticing, recognizing, understanding, and comprehending, but also includes such things as determination, mental effort, and even feelings and opinions in addition to more intellectual elements.…”
Section: Implicit Theories Of Intelligence Across Culturesmentioning
confidence: 93%
“…The Chinese-language-schooled group, however, tended to rate verbal skills as less important than did the English-language-schooled group. Moreover, in an earlier study, Chen, Braithwaite, and Huang (1982) found that Chinese students viewed memory for facts as important for intelligence, whereas Australian students viewed these skills as of only trivial importance. Das (1994), also reviewing Eastern notions of intelligence, has suggested that in Buddhist and Hindu philosophies, intelligence involves waking up, noticing, recognizing, understanding, and comprehending, but also includes such things as determination, mental effort, and even feelings and opinions in addition to more intellectual elements.…”
Section: Implicit Theories Of Intelligence Across Culturesmentioning
confidence: 93%